1991
DOI: 10.1300/j045v02n02_05
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Therapeutic Health Program for the Black Elderly

Abstract: This paper evaluates the effectiveness of a therapeutic health program which was offered in 1988 to the black elderly living in subsidized high-rise apartments in Nashville. The pre-program data (of 1987) indicated distinct differences in that the elderly living in the high-rises had significantly more medical problems, higher levels of depression, and smaller social support networks than those living in their own single dwelling homes. The therapeutic program included various modules such as cognitive and gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In some studies, therapeutic programs, similar to the program implemented in the present study, were found to significantly reduce depression and enhance other measures of psychosocial functioning for both African American and Caucasian program participants (Husaini, 1995;Husaini et al, 1990). Moreover, a review of research focusing on the effects of group and individual mental health treatments suggest equal benefits for African American and Caucasian participants (U.S. Department of Health & Human Services, 1999).…”
Section: Group Therapy For the Elderlymentioning
confidence: 61%
“…In some studies, therapeutic programs, similar to the program implemented in the present study, were found to significantly reduce depression and enhance other measures of psychosocial functioning for both African American and Caucasian program participants (Husaini, 1995;Husaini et al, 1990). Moreover, a review of research focusing on the effects of group and individual mental health treatments suggest equal benefits for African American and Caucasian participants (U.S. Department of Health & Human Services, 1999).…”
Section: Group Therapy For the Elderlymentioning
confidence: 61%
“…The high-rise residents showed a higher incidence of depression, schizophrenia and phobias than the community residents (Husaini, Moore & Castor, 1991; Castor, Whitten-Stovall, Moore et al, 1990). Unfortunately, the high-rise group was poorer, less educated, less likely to be married, reported more medical problems and had fewer social contacts, so conclusions are difficult to draw from this study.…”
Section: Strain Crowding and Mental Health In High-rises Versus Othementioning
confidence: 69%
“…The latter was also reported in a different college dormitory study (Wilcox & Holahan, 1976), one that added that perceived social support and involvement declined with height within buildings. Social support also was lower among elderly African-Americans in a high rise than among elderly African-Americans in nearby low-rises (Husaini et al, 1990), although the two groups were dissimilar in other ways, too, which may have had an influence.…”
Section: Housing Form and Prosocial Behaviormentioning
confidence: 94%
“…'s (1996) study. Further, as discussed in the literature (Manfredi & Pickett 1987, Husaini et al . 1990), the respondents also reported that illness was a stressful event that they encountered.…”
Section: Discussionmentioning
confidence: 88%